2020
DOI: 10.1111/1756-185x.13922
|View full text |Cite
|
Sign up to set email alerts
|

The conundrum of juvenile spondyloarthritis classification: Many names for a single disease? Lesson learned from an instructive clinical case

Abstract: Pediatric rheumatic diseases are often characterized by an evolving phenotype, resulting in diagnostic dilemma for physicians involved in their management. Although several classification criteria are used in childhood to uniform patients’ diagnoses, several conditions share similar clinical features and therefore their classifications may overlap or be ambiguous. This is particularly paradigmatic for the classification of juvenile spondyloarthritis (JSpA), as the currently available criteria do not encompass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Moreover, chronic recurrent multifocal osteomyelitis (CRMO) was suggested to be an unusual form of SpA by several authors and Vittecoq et al 9 showed that some of the patients with CRMO developed SpA. The insightful report by Maniscalco et al 1 also supports this perspective.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, chronic recurrent multifocal osteomyelitis (CRMO) was suggested to be an unusual form of SpA by several authors and Vittecoq et al 9 showed that some of the patients with CRMO developed SpA. The insightful report by Maniscalco et al 1 also supports this perspective.…”
mentioning
confidence: 94%
“…We read with great interest the paper titled “The conundrum of juvenile spondyloarthritis classification: Many names for a single disease? Lesson learned from an instructive clinical case” by Maniscalco et al 1 which emphasizes the complexity of the clinical phenotypes of juvenile spondyloarthropathies (JSpA). All pediatric rheumatologists face these evolving phenotypes of these groups of diseases in their daily practice.…”
mentioning
confidence: 99%
“…As mentioned previously, ErA is a special case in that it is also a jSpA. 5 Spondyloarthropathies (SpAs) are oligoarticualar, seronegative rheumatological disorders characterized by enthesitis, HLA-B27 positivity, and axial skeletal involvement. These conditions range from ErA, which is an undifferentiated disease seen exclusively in children, to differentiated adult disease such as ankylosing spondylitis.…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of clinical manifestations of rheumatic diseases make the diagnosis a difficult one. 5 While sacroiliitis in addition to inflammatory bowel disease can lead to a diagnosis of ErA, a diagnosis of chronic nonbacterial osteomyelitis (CNO) syndrome can be reached with the addition of multiple foci of painful swollen bone. If psoriasis were also present in addition to the previous symptoms, conditions to be considered may include CNO syndrome, synovitis, acne, pustulosis, hyperostosis, osteomyelitis (SAPHO) syndrome, and undifferentiated JIA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation